Sustainable Practice Guide + Meter - Korae, Eva; Achilleos, Konstantina Niina; Vënëlainen, Tuomas (My University, 2025)
he Sustainable Practice Meter + Guide was developed in Limassol, Cyprus and it is proposed as a response to the apparent lack of cost effective and straightforward tools to reflect on handicraft outcomes. Other sustainability assessment tools appear to be too demanding and too complicated to be implemented for small scale production and are usually used to assess factory production. The sustainable practice meter + guide is presented here in the form of an interactive poster. It was created by makers for makers to evaluate their work’s sustainable qualities, according to local particularities and it sprung from personal observations while practicing sustainable making. It was developed through a round table discussion at WIP International Festival 2023 (Nicosia, Cyprus) and implementation with fifteen craftspeople from accross Europe ranging from fashion to jewellery or woodwork. The findings were supported by literary research. In addition and to test it’s limits, twenty students from the BA Multimedia and Graphic Arts, Cyprus University of Technology (Product Design, third year elective) were asked to evaluate their projects’ sustainable qualities with it. It was first presented at Biennial International Conference for the Craft Sciences in Mariestad, Sweden (Oct 2025). It is based on the ‘Wheel of Life’ model, essentially borrowed from contexts of Coaching and Psycotherapy, which makes it ideal for honest self reflection on a process or object. It is another option in the toolbox for anyone eager to explore and acquire knowledge about their own processes, while discovering their needs and challenges.
Keywords: Sustainability Guide; Sustainability Metric; Green Design; Handicraft; Circular Economy; Sustainability Assessment